INFLUENCE OF SPORTS EXERCISES ON STUDENT FLEXIBILITY INDICATORS - Krasnikova, O.S.; Korichko, A.V.; Savelyeva, Yu.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the influence of sports activities on the indicators of flexibility among representatives of student youth on the basis of a comparative analysis. Methods and structure of the study. During the experiment, students of the 1st and 2nd year, engaged in sports-oriented groups, took part in the following areas: cyclic sport (swimming), mixed (volleyball) and acyclic, power (athletic gymnastics). To study the degree of influence of sportsized areas on flexibility indicators, 102 students were tested at the end of the semester. Flexibility was assessed according to five standards: symmetrical indicators, mobility of the shoulder joint and spinal column were studied. Results and conclusions. A comparative analysis of the indicators of students attending various sports areas showed that the greatest effect of developing flexibility is achieved in the process of swimming. The impact of the aquatic environment on the body and the cyclical nature of the work have a beneficial effect on flexibility indicators, including leading to harmonious development. As a result of playing volleyball, the flexibility of the left side of the body is actively developing and the mobility of the shoulder joint of the right hand is increasing. There is an asymmetry in the development of the flexibility of the right and left sides, both in boys and girls. Ineffective in the development of flexibility, athletic gymnastics was noted, as indicated by the testing data of representatives of student youth. Excessively developed strength abilities stimulate an increase in the diameter of the muscle fiber, which negatively affects the manifestation of flexibility in those involved. With the help of a comparative analysis in the studied sportsized areas, significant gender differences in the development of flexibility were found. In particular, the indicators of female representatives’ flexibility are better developed in comparison with young men who go in for volleyball and athletic gymnastics. The exception is young men involved in volleyball, in which the indicators of mobility of the shoulder joint of the right hand prevail with similar values ​​of girls. There were no gender differences in the results of symmetrical tests among representatives of the sportsized direction of a cyclic nature (swimming).